Johan Östling, Erling Sandmo, David Larsson Heidenblad, Anna Nilsson Hammar & Kari H. Nordberg (eds), Circulation of Knowledge. Explorations in the History of Knowledge. - Dahlberg, Julia (Historisk Tidskrift för Finland, 2018)
-